Metastatic Crohn's disease in a boy presenting with genital swelling. Issue 6 (23rd September 2020) - Mazzoni, Daniel; Bodapati, Sarath; Mortimore, Rohan; Davies, Janene; Wheller, Laura
Abstract: Cutaneous manifestations of Crohn's disease are uncommon and occasionally can affect the genitals with varying symptomatology. When cutaneous features precede or occur in the absence of GI symptoms, this condition may remain undiagnosed. We report the case of a 14‐year‐old boy who presented for evaluation of persistent penile edema with clinicopathological features consistent with a diagnosis of genital metastatic Crohn's disease, successfully treated with infliximab.